2016
DOI: 10.1038/ng.3595
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association of multiple complex traits in outbred mice by ultra-low-coverage sequencing

Abstract: Two bottlenecks impeding the genetic analysis of complex traits in rodents are access to mapping populations able to deliver gene-level mapping resolution, and the need for population specific genotyping arrays and haplotype reference panels. Here we combine low coverage sequencing (0.15X) with a novel method to impute the ancestral haplotype space in 1,887 commercially available outbred mice. We mapped 156 unique quantitative trait loci for 92 phenotypes at 5% false discovery rate. Gene-level mapping resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
189
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 136 publications
(197 citation statements)
references
References 58 publications
8
189
0
Order By: Relevance
“…In general, heritability estimates were 119 larger for physiological traits than for behavioral traits (Fig.3B, Supplemental Table S2), which is 120 consistent with findings in other rodent GWAS (Parker et al 2016;Nicod et al 2016;Rat Genome 121 Sequencing and Mapping Consortium et al 2013). Mean heritability was 0.355 (se=0.045) for 122 physiological traits and 0.168 (se=0.038) for behavioral traits (conditioned place preference, locomotor 123 sensitization, and habituation to startle were not found to have a genetic component and were excluded 124 from the mean).…”
supporting
confidence: 75%
“…In general, heritability estimates were 119 larger for physiological traits than for behavioral traits (Fig.3B, Supplemental Table S2), which is 120 consistent with findings in other rodent GWAS (Parker et al 2016;Nicod et al 2016;Rat Genome 121 Sequencing and Mapping Consortium et al 2013). Mean heritability was 0.355 (se=0.045) for 122 physiological traits and 0.168 (se=0.038) for behavioral traits (conditioned place preference, locomotor 123 sensitization, and habituation to startle were not found to have a genetic component and were excluded 124 from the mean).…”
supporting
confidence: 75%
“…Genetic variability combined with environmental factors is the underlying cause of individual differences. In a recent study, we found that an allelic variant of the Met gene conferring an increase in mouse soleus weight had a decreasing effect on the fast-twitch EDL and gastrocnemius muscles (Nicod et al, 2016). Hence, it is reasonable to hypothesize that the adaptive response might also differ between the muscles.…”
Section: Discussionmentioning
confidence: 97%
“…Integration of these two novel genome sequences with the growing catalog of known M. musculus genetic variation will provide a valuable resource to researchers using mouse models to study a wide variety of biological processes, including karyotype evolution (Chmátal et al 2014), speciation (Payseur and Place 2007), protein evolution (Karn et al 2008; Stempel et al 2016), gene duplications (Laukaitis et al 2008; Morgan et al 2016b), X-chromosome inactivation (Calaway et al 2013), and disease-associated quantitative traits (Cervino et al 2005; Perez et al 2013; Nicod et al 2016). …”
Section: Resultsmentioning
confidence: 99%